Risk Assessment in Pulmonary Arterial Hypertension According to Right Atrial Pressure and Correlation Between Mean Pulmonary Arterial Pressure with Right Atrial Pressure in Uncorrected Atrial Septal Defect Patients at Dr. Sardjito General Hospital - Krisnawati D., et al (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Risk Assessment in Pulmonary Arterial Hypertension According to Right Atrial Pressure and Correlation Between Mean Pulmonary Arterial Pressure with Right Atrial Pressure in Uncorrected Atrial Septal Defect Patients at Dr. Sardjito General Hospital